Dutch Strategy in West Aceh (Aceh War, 1873-1906): Strategi Belanda di Aceh Barat (Perang Aceh, 1873-1906) - Rahmatul Aulia (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
The western region of the Aceh Darussalam Kingdom began to be opened and developed in the 16th century on the initiative of the Sultan of Aceh, then continued by Sultan Iskandar Muda by bringing in the Aceh Rayeuk and Pidie people. The opening of the Suez Canal in 1869 caused international traffic between East and West to become increasingly busy. This influenced international competition in winning trade and fighting over colonial lands in Asia. After the Aceh Besar region was conquered, the geography of West Aceh, which was very politically and economically strategic, also had to be conquered, in order to maintain this very strategic trade route. On the other hand, the appointment of Teuku Umar as Commander of the Aceh War, whose territory was in western Aceh, meant that the Dutch were obliged to conquer this region in order to be able to run their government.